2017
DOI: 10.1111/cdev.12811
|View full text |Cite
|
Sign up to set email alerts
|

From Autonomy to Divinity: The Cultural Socialization of Moral Reasoning in an Evangelical Christian Community

Abstract: This study examined moral reasoning in parent-child conversations within a U.S. evangelical Christian community. The goal was to identify social-communicative processes that may promote the development of Divinity in children's moral reasoning. Sixteen parent-child dyads (6-9 years old) discussed hypothetical moral vignettes about failures to help peers in need. Analyses revealed that Divinity typically co-occurred with Autonomy in these conversations and that such co-occurrences typically happened through thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Numerous studies conducted in the United States (within different Christian belief groups), and also in China (with Confucianism, Taoism, and Buddhism being practiced) and Turkey (with an Islamic majority) showed that personal religiosity has an influence on the importance of Divinity in moral reasoning (e. g. Haidt et al, 1993; Jensen & McKenzie, 2016; Tepe et al, 2016; Vasquez et al, 2001; Zhang & Li, 2015). DiBianca Fasoli (2018) concluded that, although Divinity may be found in religious as well as non-religious groups, “religiously conservative groups may uniquely regard Divinity as a generalizable obligation” for their life (p. 1659). Islam has an important influence on everyday life in Indonesia and even in the Pancasila, the principle “Belief in the One and Only God” is at the heart of all five rules, which could be interpreted as an overarching moral obligation (Baidhawy, 2007; Weatherbee, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies conducted in the United States (within different Christian belief groups), and also in China (with Confucianism, Taoism, and Buddhism being practiced) and Turkey (with an Islamic majority) showed that personal religiosity has an influence on the importance of Divinity in moral reasoning (e. g. Haidt et al, 1993; Jensen & McKenzie, 2016; Tepe et al, 2016; Vasquez et al, 2001; Zhang & Li, 2015). DiBianca Fasoli (2018) concluded that, although Divinity may be found in religious as well as non-religious groups, “religiously conservative groups may uniquely regard Divinity as a generalizable obligation” for their life (p. 1659). Islam has an important influence on everyday life in Indonesia and even in the Pancasila, the principle “Belief in the One and Only God” is at the heart of all five rules, which could be interpreted as an overarching moral obligation (Baidhawy, 2007; Weatherbee, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Psychologists have in recent years increasingly highlighted the culturally situated nature of human development. Scholars of identity (Berry, Phinney, Sam, & Vedder, 2006;Nguyen & Brown, 2010), morality (DiBianca Fasoli, 2017;Jensen & McKenzie, 2016;Miller, 2005), cognition (Correa-Ch avez & Rogoff, 2009), and intelligence (Sternberg, 2014) have foregrounded the role of culture in shaping fundamental developmental processes. This article points to the role of cultural change in shaping adolescent practices, framings of self, and negotiations of social hierarchies encountered in their everyday lives.…”
mentioning
confidence: 99%
“…These narratives carry implications for community members’ meaning‐making about their moral experiences and Divinity reasoning across the life course. Another study focusing on the moral conversations of evangelical Christian parent‐child dyads found that parents were more likely to use Divinity, and children were more likely to use Autonomy, reasoning (DiBianca Fasoli, ). It was further shown that conversations typically involved multiple ethics—especially Divinity and Autonomy—and that parents employed Divinity justifications to align with or legitimize their child's Autonomy reasoning, to counter their child's Autonomy justification, and to scaffold Divinity reasoning through Autonomy reasoning.…”
Section: Morality Divinity and Culturementioning
confidence: 99%
“…To determine whether Divinity reasoning was used in isolation or co‐arose alongside other lines of reasoning, interviews were labeled as either “divinity alone” (if Divinity justifications occurred only alongside other Divinity justifications) or “divinity co‐occurrence” (if Divinity justifications co‐occurred alongside Community or Autonomy justifications). This follows DiBianca Fasoli's () ethical co‐occurrence analytic procedure.…”
Section: Ethic Of Divinity Reasoningmentioning
confidence: 99%
See 1 more Smart Citation